2010
DOI: 10.1021/la9044495
|View full text |Cite
|
Sign up to set email alerts
|

Sliding of Water Droplets on Microstructured Hydrophobic Surfaces

Abstract: Sliding behaviors of liquid droplets on solid surfaces are among the fundamental results of wettability. To remedy the lack of quantitative correlation between sliding angle and roughness of the surface, which is known to be effective at enhancing wettability, we report in this paper the observation that the onset of water droplets sliding under gravity on inclined micropillar-structured hydrophobic surfaces always starts with detachment of the rear contact lines of the droplets from the pillar tops. We also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
129
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(143 citation statements)
references
References 24 publications
13
129
0
Order By: Relevance
“…In other words, the larger the solid area fraction, the longer perimeter of contact line, and the stronger the adhesive forces between the water droplet and the solid surface. This is in agreement with available research findings [20,21].…”
Section: Measurement Of Dynamic Contact Angles and Internal Velocity supporting
confidence: 94%
“…In other words, the larger the solid area fraction, the longer perimeter of contact line, and the stronger the adhesive forces between the water droplet and the solid surface. This is in agreement with available research findings [20,21].…”
Section: Measurement Of Dynamic Contact Angles and Internal Velocity supporting
confidence: 94%
“…This can be described by the contact angle hysteresis, defined as the difference between the advancing and receding angle, and the sliding angle where the droplet start to roll off the surface [19]. The kinetics of wetting is much less understood than for droplets in equilibrium, so most of the current theoretical research is focusing on this area [18,20,21]. It is believed that a low contact hysteresis is a requirement of a stable Cassie-Baxter wetting state [22].…”
Section: Theoretical Conceptsmentioning
confidence: 99%
“…The basic principle is to transfer a positive or negative image from a mask by exposing a photoreactive polymer with a UV-, electron-or X-ray source [49]. Due to the wellcontrolled reproducible results, it has mostly been used to create surfaces for examining the superhydrophobic phenomenon and the connections between surface structures and wetting behaviour [12,18,21,23,37,[50][51][52][53][54]. One of the earliest works by Öner et al [18] examined the wetting quantitatively on a micro-textured surface, using photolithography and subsequent etching in silicon to produce three-dimensional pillars with various size, shapes and separations.…”
Section: Photolithographymentioning
confidence: 99%
“…The channel surface wettability considered includes the contact angle θ channel equal to 70 • , 45 • , 110 • , and 140 • , respectively, corresponding to Case 3-6 shown in Table 1. The associated sliding angle α channel for the channel surface is also considered and obtained from a correlation between the contact angle and the sliding angle widely adopted in the previous studies [33,34], as shown below:…”
Section: Effect Of the Channel Surface Wettabilitymentioning
confidence: 99%